Peran Brand Trust pada Pengaruh Online Customer Review dan Perceived Value terhadap Purchase Intention - Amrina Rosada; Wahyu Setiawan (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze the influence of Online Customer Review (X₁) and Perceived Value (X₂) on Purchase Intention (Y), with Brand Trust (Z) as a mediating variable among consumers who purchase Samsung smartphones through the Samsung Official Store on Shopee. The research employs a quantitative approach by conducting a survey of 100 respondents in Semarang City who have either purchased or intend to purchase Samsung smartphones via Shopee. Data analysis was performed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results reveal that Online Customer Review does not have a significant direct effect on Purchase Intention but has a positive and significant impact on Brand Trust. Perceived Value has a significant influence on Purchase Intention both directly and indirectly through Brand Trust mediation. Additionally, Brand Trust positively and significantly affects Purchase Intention, confirming its role as a mediator between Online Customer Review and Perceived Value toward Purchase Intention. These findings suggest that the Samsung Official Store on Shopee should improve the quality of customer reviews and the perceived value of products to strengthen brand trust and encourage consumers’ purchase intentions